Public relations, propaganda and poison: a case study of South African press coverage of the Vanderbijlpark water pollution crisis and Mittal Steel - Malan, Ryan (My University, 2010)
Abstract This study provides an account of the media coverage from The Star and The Citizen that dealt with the topic of water pollution in the Vanderbijlpark area. The first research question of this study asked how much coverage this issue had received in the two newspapers analysed. The second research question asked what this coverage of the issue looked like. The quantitative findings revealed that very few articles dealt with this topic from either publication, especially in relation to the corporation responsible for this pollution, namely Mittal Steel (previously Iscor). The qualitative findings involved thematic content analysis revealing themes such as legal conflict, sourcing, greenwashing and environmental reporting. A particular concern raised by this study was the use of sources and attribution in the articles. The local community was provided with very few opportunities to express their own concerns about the water pollution problem. It was found that most articles made extensive use of ‘official sources’ and representatives from the corporation and various government departments. A very limited number of articles provided the local community with public representation and described the situation in detail. This study concluded that these two publications had in fact failed in their responsibilities as the ‘fourth estate’ by providing very little coverage of the issue and by relying on official sources and public relations personnel.